PENERAPAN METODE PEMBELAJARAN HYPNOTEACHING DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS X.3 PADA MATA PELAJARAN AKIDAH AKHLAK - Muh. Nurdin Halid; Nurlaela; Subaedah; Akhmad Syahid; Mustamin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Preliminary observations in class X.3 at MAN 1 Makassar City indicated that students' learning motivation in the Akidah Akhlak (Islamic Creed and Ethics) subject was low, characterized by a lack of attention, limited active questioning, and minimal participation in the learning process; furthermore, many students had not yet met the Minimum Mastery Criteria (KKM). This study aimed to (1) examine the implementation of the Hypnoteaching method in the Akidah Akhlak subject in class X.3 at MAN 1 Makassar City, and (2) determine the improvement in students' learning motivation following the implementation of the Hypnoteaching method. The study employed Classroom Action Research (CAR) using both qualitative and quantitative approaches. The results showed that (1) the implementation of the Hypnoteaching method—incorporating the stages of pacing, leading, positive words, modeling, and positive reinforcement—successfully created a more conducive learning environment and enhanced students' attention, active engagement, cooperation, and sense of responsibility during Akidah Akhlak lessons. (2) Students' learning motivation improved across each cycle. The average motivation score rose from 69.43 in the pre-cycle stage to 79.19 in Cycle I and 87.97 in Cycle II. The mastery percentage also increased from 51.35% in the pre-cycle stage to 64.86% in Cycle I, reaching 91.89% in Cycle II, thereby meeting the study's success indicators. The study concludes that the Hypnoteaching method is effective in increasing students' learning motivation in the Akidah Akhlak subject in class X.3 at MAN 1 Makassar City. It is recommended that teachers implement the Hypnoteaching method consistently and adapt it to the students' characteristics to ensure continued improvement in both learning motivation and the quality of instruction.